POTRET KEBERAGAMAN DAN KEARIFAN LOKAL DI GUNUNG KAWI - Bambang Hariyanto (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2017)
Local wisdom in Gunung Kawi is one of the interesting miniatur in Indonesia, and it is depicting of the variety in the belief system of this nation. Religious tourism object at Gunung Kawi located near from Malang city, east Java. There is holly person in this place, they are Eyang Djoego and RM Imam Soedjono. They have been respected by the society because of their character as the role model. They were as loyal guard troops of Diponegoro when happened Java War 1825-1830, and they have family relation with Mataram Kingdom. This research aims at describing the part of the fact of local wisdom among the society and the pilgrims in Kawi mountain. Data gather with direct observation and interview trough pilgrims, public figure in Kawi mountain. This research uses Anthropolgy Linguistics approach. The data display with literary texts of other sources. Furthermore, data are analyzed using descriptive analysis. The result shows that tolerance and togetherness attitude in Kawi mountain because of the similarities understanding among others about the essence of their ritual. It could be seen during their the ritual practice although they have different belief system and religion